The Role of Presenilin and its Interacting Proteins in the Biogenesis of Alzheimer’s Beta Amyloid - Verdile, Giuseppe; Gandy, S.; Martins, R. (Kluwer Academic Publishers-Plenum Publishers, 2007)
The biogenesis and accumulation of the beta amyloid protein (Aß) is a key event in the cascade of oxidative and inflammatory processes that characterises Alzheimer’s disease. The presenilins and its interacting proteins play a pivotal role in the generation of Aß from the amyloid precursor protein (APP). In particular, three proteins (nicastrin, aph-1 and pen-2) interact with presenilins to form a large multi-subunit enzymatic complex (?-secretase) that cleaves APP to generate Aß. Reconstitution studies in yeast and insect cells have provided strong evidence that these four proteins are the major components of the ?-secretase enzyme. Current research is directed at elucidating the roles that each of these protein play in the function of this enzyme. In addition, a number of presenilin interacting proteins that are not components of ?-secretase play important roles in modulating Aß production. This review will discuss the components of the ?-secretase complex and the role of presenilin interacting proteins on ?-secretase activity.